Food Diversity and Indigenous Food Systems to Combat Diet-Linked Chronic Diseases. (2nd September 2019) - Sarkar, Dipayan; Walker-Swaney, Jacob; Shetty, Kalidas
ABSTRACT: Improving food and nutritional diversity based on the diversity of traditional plant-based foods is an important dietary strategy to address the challenges of rapidly emerging diet- and lifestyle-linked noncommunicable chronic diseases (NCDs) of indigenous communities worldwide. Restoration of native ecosystems, revival of traditional food crop cultivation, and revival of traditional knowledge of food preparation, processing, and preservation are important steps to build dietary support strategies against an NCD epidemic of contemporary indigenous communities. Recent studies have indicated that many traditional plant-based foods of Native Americans provide a rich source of human health–relevant bioactive compounds with diverse health benefits. Based on this rationale of health benefits of traditional plant-based foods, the objective of this review is to present a state-of-the-art comprehensive framework for ecologically and culturally relevant sustainable strategies to restore and integrate the traditional plant food diversity of Native Americans to address the NCD challenges of indigenous and wider nonindigenous communities worldwide.